Sistem Informasi Pembayaran Sumbangan Penunjang Pendidikan (SPP) Santri Pesantren Tahfidz Adh Dhuhaa Tangerang - Elly , Mega Nurmalasari; Hati, Kusuma (Jurnal Kajian Ilmiah, 2020)
Abstract The Islamic Boarding School Tahfidz Adh Dhuhaa needs an information system specifically to overcome problems related to the management of SPP payments for students that are increasing every year. So far, the management of Santri SPP payments is done by inputting payment data with the Microsoft Excel application so that it still often experiences obstacles when searching for data and providing Santri SPP payment reports. Because of that, it is needed a web-based payment information system for students-based SPP in order to facilitate the treasurer of the Islamic Boarding School Tahfidz Adh Dhuhaa in managing the SPP payment. The SPP Santri Payment Information System includes management of student data, monthly SPP payment data, and producing a report. With this system, it is hoped that it will be easier for treasurers of the Islamic Boarding School Tahfidz Adh Dhuhaa to manage students' tuition payment data easily and quickly. Keywords: Student, Information System, Educational Support Contribution, Waterfall Model Abstrak Pesantren Tahfidz Adh Dhuhaa membutuhkan sebuah sistem informasi khususnya untuk mengatasi permasalahan yang terkait dengan pengelolaan pembayaran SPP para santri yang semakin bertambah setiap tahunnya. Selama ini pengelolaan pembayaran SPP Santri dilakukan dengan menginput data pembayaran dengan aplikasi microsoft excel sehingga masih sering mengalami kendala pada saat mencari data dan memberikan laporan pembayaran SPP santri. Karena itu dibutuhkan Sistem Informasi Pembayaran SPP santri berbasis web agar dapat mempermudah bendahara Pesantren Tahfidz Adh Dhuhaa dalam mengelolah pembayaran SPP tersebut. Sistem Informasi Pembayaran SPP santri ini meliputi pengelolaan data santri, data pembayaran SPP setiap bulan, sampai menghasilkan sebuah laporan. Dengan adanya sistem tersebut di harapkan dapat mempermudah bendahara Pesantren Tahfidz Adh Dhuhaa dalam melakukan pengolalaan data pembayaran SPP santri dengan mudah dan cepat. Kata kunci: Santri, Sistem Informasi, Sumbangan Penunjang Pendidikan (SPP), Model Waterfall